Long-term effectiveness and safety of lacosamide as adjunctive therapy in children and adolescents with refractory epilepsy: a real-world study - Ting Zhao; Lu-hai Yu; Hui-lan Zhang; Jing Yu; Jie Feng; Ting-ting Wang; Yan Sun; Hong-jian Li (BMC, 2023)
Abstract Purpose The effectiveness and tolerability of lacosamide (LCM) among Chinese children and adolescents with refractory epilepsy has not yet been established. Therefore, the objective of this study was to assess the effectiveness and tolerability of LCM among children and adolescents with refractory epilepsy in Xinjiang, Northwest China. Methods Effectiveness was assessed by measuring changes in seizure frequency at 3, 6 and 12 months compared with baseline. Patients that achieved ≥ 50% reduction in the frequency of all seizures per month, relative to baseline, were considered to be responders. Results 105 children and adolescents with refractory epilepsy were enrolled in the study. The responder rates were 47.6%, 39.2%, and 31.9%, respectively at 3, 6, and 12 months. Seizure freedom rates were 32.4%, 28.9%, and 23.6% at 3, 6, and 12 months, respectively. The retention rates at 3, 6, and 12 months were 92.4%, 78.1%, and 69.5%, respectively. The maintenance dose of LCM within the responder group (8.2 ± 4.5 mg·kg− 1·d− 1) was significantly higher compared to the non-responder group (7.3 ± 2.3 mg·kg− 1·d− 1) (p < 0.05). At first follow-up, 44 patients (41.9%) reported experiencing at least one treatment-emergent adverse events. Conclusion This real-world study of children and adolescents validated that LCM was both an effective and well-tolerated treatment option for the treatment of refractory epilepsy.